(untitled) (UNED Research Journal, 2014)
ABSTRACT: Reasons for culling and number of bovine females (Bos taurus, Artyodactila: Bovidae) culled in plant in Costa Rica from 2008 through 2009. It is important for the livestock sector to keep regular checks on production, reproduction and industrialization to prevent any changes that may affect it, and use the information as a basis for decision-making. The main purpose of this job was to define the quantity and main causes for culling bovine females in one of the most important slaughterhouse in Costa Rica. From October 2008 to December 2009, all the bovine females sent to Cooperativa Matadero Nacional de Montecillos R.L., Alajuela, Costa Rica; this coop represents up to 20% of the national herd slaughtered. During the period of the study, the percentage of cows culled was 50.57%, from this, 51.44% were pregnant in stages from conceptuses to fetuses in the last days before calving. There is a 38.16% of young bovine females that are harvested, some of them without the chance for calving. Among people associated to the Coop the causes for harvesting cows are: old cows (19.6%), selection pressure (18.2%), lack of money (16.1%), reproductive issues (16.1%), shortage of feed for the animals (18.2%) and others like sicknesses and market strategies (16.0%). Some of these causes can be solved if farms are administered correctly avoiding losses for farmers and the decrease of the national herd. KEY WORDS: Pregnant cows, bovine herd, harvest of animals, extractions, gestation.